RESPONSE OF Citrus aurantifolia TO THE INHIBITION ZONE OF THE Aeromonas salmonicida BACTERIA IN TILAPIA (Oreochromis niloticus) - Adellia Rindi Putri Utami; Sri Oetami Madyowati; Nurul Hayati; Maria Agustini (Jurnal Perikanan Unram, 2024)
The impact of using synthetic antibacterials creates a number of new cultivation problems, including: Bacterial resistance, retention of toxic substances and residues in the consumer's body. You need antimicrobial ingredients that can kill bacteria, one of which is the use of lime juice. The aim is to find out how strongly Citrus aurantifolia inhibits the bacteria Aeromonas salmonicida from Oreochromis niloticus. Using a completely randomized design (CRD) with five treatments. The results showed that the diameter of the inhibition zone for each Treatment A was 10.8 mm, Treatment B 12.8 mm, Treatment C 14.7 mm, Treatment D 16.7 mm, and Treatment E 19.1 mm. The relationship between administration of lime juice and the average diameter of the inhibition zone produced in inhibiting the growth of Aeromonas salmonicida bacteria shows a response that increases with increasing dose. Based on the Anova test using F (0.000) > F table at the 5% level of significance, lime juice (Citrus aurantifolia) has an effect on inhibiting the growth of Aeromonas salmonicida in each treatment.